Un système de sépulture égalitaire en territoire tarquinien - Edwige Lovergne (Frontière·s)
The study of Musarna’s Hellenistic necropolis has drawn attention to a particular type of grave, identified by 19th-century archaeologists as tomba a cassone. Those large cube-shaped pits are dug into the tufa bedrock and apart from various internal arrangements –single or double burials, inhumation or cremations– they always have a similar layout and same structural characteristics. This type of grave was thought to be attested exclusively in Musarna and its surroundings but we have registered 83 graves a cassone of ‘Musarna type’, distributed throughout the Tarquinian territory. The diffusion of these graves is limited to the end of the 4th and the beginning of the 3rd century BC proves to be closely connected to the creation of small oppida in the hinterland of the Etruscan metropolis on the eve of the last conflict against Rome. This article aims to make a first inventory of this ‘new’ typology, as these graves have never been thoroughly studied, although several of them have returned rich funerary finds, comparable to those of local aristocratic chamber graves.